Naturally Occurring tRNAs With Non-canonical Structures - Krahn, Natalie; Fischer, Jonathan T.; Söll, Dieter (Frontiers in Microbiology, 2020)
Transfer RNA (tRNA) is the central molecule in genetically encoded protein synthesis. Most tRNA species were found to be very similar in structure: the well-known cloverleaf secondary structure and L-shaped tertiary structure. Furthermore, the length of the acceptor arm, T-arm, and anticodon arm were found to be closely conserved. Later research discovered naturally occurring, active tRNAs that did not fit the established ‘canonical’ tRNA structure. This review discusses the non-canonical structures of some well-characterized natural tRNA species and describes how these structures relate to their role in translation. Additionally, we highlight some newly discovered tRNAs in which the structure–function relationship is not yet fully understood.